ETMR-04. Embryonal tumor with multi-layered rosettes (ETMR) located in the brainstem: a case report on clinical decision-making and a multimodal, interdisciplinary treatment approach including interstitial brachytherapy. (3rd June 2022) - Jünger, Stephanie T; Rueß, Daniel; Goldbrunner, Roland; Gielen, Gerrit H; Peitsch, Torsten; Johann, Pascal; Landgraf, Pablo; Simon, Thorsten; Ruge, Maximilian I
Abstract: OBJECTIVE: Embryonal tumors with multi-layered rosettes (ETMR) (CNS WHO grade 4) comprise a rare and malignant tumor type affecting predominantly infants below 3 years of age. The treatment consists of maximal safe surgical resection, irradiation, and intensive medulloblastoma type chemotherapy. Despite aggressive treatment, the prognosis of these patients remains poor, especially for brainstem tumors. We present the case of a male infant diagnosed with a brainstem ETMR, successfully treated with an interdisciplinary multimodal approach, including stereotactic interstitial brachytherapy. RESULTS: A 19 month old boy first presented with hemiparesis, intermittent bradycardia and reduced consciousness. Initial imaging showed a brainstem lesion with characteristic features of a diffuse intrinsic pontine glioma (DIPG). We performed stereotactic biopsy to confirm the diagnosis and initiated temozolomide treatment. While the pathology result was still pending, the boy's clinical condition deteriorated to a soporic state with stretch synergisms. By emergency open surgery, partial resection was achieved. Eventually, the patient recovered rapidly. After the diagnosis of ETMR was established, medulloblastoma type chemotherapy (systemic carboplatin/etoposide; intrathecal methotrexate) was administered. After two cycles, the patient showed only residual right-sided hemiparesis. However, imaging demonstrated only a minimal reduction of the tumor size. Therefore, stereotactic interstitial brachytherapy using 125iodine seeds and subsequent high-dose chemotherapy (HDCT) with autologous stem cell transplantation (ASCT) was performed and overall tolerated well. After two months of brachytherapy and two additional cycles of chemotherapy, the MRI showed ≥ 50% reduction in tumor volume and no neurological deficit can be clinically detected. CONCLUSION: This case indicates that stereotactic interstitial brachytherapy during intensive systemic chemotherapy is feasible. It may provide a suitable treatment for malignant infant brain tumors. Furthermore, it shows that paediatric patients are capable of recovery even after devastating neurological symptoms. Lastly, it emphasizes the importance of multidisciplinary and multimodal treatment for rare diseases.